Lesson Study Penerapan Math City Map dalam Pembelajaran Matematika - Anaguna, Nursyam; Arifin, Sartika; Aprisal; Lestari, Yusfa; Yahya, Amran; Murtafiah; Amin, Nursafitri; Manulang, Ketrin R.; Adinang (Pendidikan Matematika, FKIP Universitas Mataram, 2024)
The low quality of mathematics learning that has an impact on the lack of improvement in students' mathematics abilities is the main reason for implementing the lesson study community service activity of applying math city maps in mathematics learning. Due to this reason, the activity was carried out using a procedure that includes the stages of planning, implementation, and evaluation. The success of the community service activity was analyzed using a questionnaire on the success and satisfaction of partners distributed to 13 mathematics teachers at Majene regency. The results of the activity showed a positive influence of the activity on teachers where the average evaluation aspect reached a percentage of 88.3%. From the results of the implementation of the activity, it was also concluded that teachers were interested in implementing lesson study as an initial step in improving the quality of students' mathematics learning